Factors Determining the Southern Range Limit of Hemigrapsus sanguineus in the Western Atlantic - Luke Ashworth; Margo Harris; David L. Neu; Blaine D. Griffen (Ecology and Evolution, 2025)
ABSTRACT The southern range limit of the invasive Asian shore crab, Hemigrapsus sanguineus, along the United States East coast is further north than expected based on its native distribution. We investigated potential factors that may limit the southward spread of this species along the Mid‐Atlantic and South Atlantic bights from Virginia to South Carolina, including metabolic constraints, food availability, and habitat limitation. We searched sites identified as potential habitat for H. sanguineus to verify the presence/absence of the crab, measured the metabolic rates of crabs at their current southern range edge for comparison with previous measurements made further north on the New Hampshire coast, used digital images captured at each site to determine whether the availability of potential food decreases south of the current range limit, and used Google Earth to measure distances between suitable habitat patches north and south of the current range limit to determine whether habitat availability limits the range expansion toward the south. We encountered the species ~64 km further south than the documented range limit at Oregon Inlet, North Carolina. We found no difference in metabolism between crabs at the southern range edge compared to crabs from New Hampshire, and no consistent difference in the abundance of available food between sites north and south of the current range limit. However, we found greater distances between suitable hard‐substrate sites south of the current range limit than between sites found within the current range. We suggest that the availability of suitable habitat is the primary driver limiting the further southward range expansion of H. sanguineus.